4x-2(x+1)=5+3(3-3x)

Simple and best practice solution for 4x-2(x+1)=5+3(3-3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-2(x+1)=5+3(3-3x) equation:



4x-2(x+1)=5+3(3-3x)
We move all terms to the left:
4x-2(x+1)-(5+3(3-3x))=0
We add all the numbers together, and all the variables
4x-2(x+1)-(5+3(-3x+3))=0
We multiply parentheses
4x-2x-(5+3(-3x+3))-2=0
We calculate terms in parentheses: -(5+3(-3x+3)), so:
5+3(-3x+3)
determiningTheFunctionDomain 3(-3x+3)+5
We multiply parentheses
-9x+9+5
We add all the numbers together, and all the variables
-9x+14
Back to the equation:
-(-9x+14)
We add all the numbers together, and all the variables
2x-(-9x+14)-2=0
We get rid of parentheses
2x+9x-14-2=0
We add all the numbers together, and all the variables
11x-16=0
We move all terms containing x to the left, all other terms to the right
11x=16
x=16/11
x=1+5/11

See similar equations:

| 112-7(x-1)=84 | | 7(1-2f)+5=11f | | 2-​​1/2n=3n+16 | | 1+n=-3(1-n) | | 3/2x=12-5/2x | | -13+3x=17 | | (12x+-5)+-11)=0 | | -38(x+4)= | | -5+3n=13 | | (3n+24)+(4n+16)=180 | | 66-5=3b+6 | | 8(4x)-9(2x)+1=0 | | 25p=-125 | | 2x2+8x+8=0 | | −8w−6=−(8w+6) | | 10=x/3+8 | | x*2-36=8 | | 2a+6=2(a+6) | | 2(x+3)=8x-6 | | 2x^2+5x−8=0 | | 2x2+5x−8=0 | | -6x+4=-18+5x | | 3x+36=11 | | 2x=4/2x=4 | | 10+8r=2 | | 5y^2+16=42y | | 3x+18=4x10 | | 4m÷5=-16 | | 8xx16=128 | | 32=4v-4 | | 6x+33=45 | | 3x(x+5)-x-5=0 |

Equations solver categories